Outcomes of laparoscopic hysteropexy and supracervical hysterectomy plus cervicopexy: A retrospective study - Pei-Chen Li; Dah-Ching Ding (Tzu Chi Medical Journal)
Objectives: The objective of this study is to compare the outcomes of laparoscopic hysteropexy (LHP) and laparoscopic supracervical hysterectomy plus cervicopexy (LSHCP) for the treatment of pelvic organ prolapse (POP). Materials and Methods: We retrospectively included patients who had undergone laparoscopic sacral hysteropexy or hysterectomy plus cervicopexy between January 2015 and May 2019 at Hualien Tzu Chi Hospital, Taiwan. Age at surgery, body mass index (BMI) at admission, the initial stage of genital prolapse, operative and postoperative data, and anatomical results were recorded. Cure for uterine prolapse was evaluated objectively through vaginal examinations using the POP quantification scale. Visual analog scale (VAS) scores were recorded at 24 h postoperatively. The Mann–Whitney U-test was used to compare continuous variables. Results: A total of 23 women were included in the study; 12 had received LHP (n = 12) and 11 had received LSHCP (n = 11). No differences existed in age, parity, BMI, blood loss, or hospital stay between groups. The difference in mean surgical times between the LHP and LSHCP groups was nonsignificant (154 and 176 min, respectively;P = 0.2). VAS scores were significantly lower in the LSHCP group than in the LHP group (0.1 vs. 1.75; P = 0.004). Furthermore, mean hospital stay was significantly longer in the LSHCP group than in the LHP group (4.0 vs. 3.1 days; P = 0.016). The procedure was successful in 100% of patients (23 of 23), with no objective evidence of uterine prolapse on examination at follow-up at 6 months. Conclusion: LHP had a significantly shorter hospital stay and a higher VAS score than LSHCP. LHP and LSHCP are both feasible and effective procedures for correcting uterine prolapse.